Training: empty experience or psychological instrument? - Vieira, Talita Machado [UNESP] (Inst Brasileiro Pesquisa & Ensino Fisiologia Exercicio-ibpefex, 2019)
This paper focus on the sports training for football athletes and aims to show the relationship between teaching models adopted by coaches and the appropriation that adolescents make about contents that integrate their sporting modality. The material examined was obtained through the use of the Simple Self-Confrontation methodological device, according to the Ives Clot's Activity Clinic formulations, using the document analysis, the participant observation, the semistructured interviews and the video analysis. Considering that the moment of staying in the youth teams has the clear purpose of producing athletes for the professional football, it seems pertinent to assume that the way in which the activities are developed with the young boys interferes in the type of professional formed for the craft of football. In the analysis presented, the athletes varied between the wide dependence on the figure of the coach and the autonomy concerning to the analysis of their performances and the ability to make alterations or adjustments in order to be able to carry out their work at the moment of the game. Thus, using the theoretical-conceptual referential of Historical-Cultural Psychology, we understand the role of the coach as mediation agent of sports learning, signaling that the different pedagogical styles lead to the formation of athletes with equally distinct characteristics, insofar as they interfere in the appropriation that the subject does about the contents. In the course of the discussions about the smart athlete, we must observe which pedagogical strategies seem to favor the formation of this type of athlete.
Keywords: Football; Sport Psychology; Learning; Mediation